Isolation of Mycobacteria spp from Rats - Abbas, Maysoon Sabah (The Iraqi Journal of Veterinary Medicine, 2008)
The main aim of this study is to detect infection of Wild brown rats withMycobacteria . fourtyone Wild brown rats were collected from variousquarters of Baghdad city during the period 29/5/2004 – 30/10/2004 .fourty one rats collected from college of Veterinary Medicine farmBaghdad University and from farm of Abu – Ghraib , Baghdad –ALGedida , AL – Mahmoedia , AL – hurrea . In this study after collectionof rats the post mortem change was studied and take one hundred twentythree sample of Lung , Liver and Spleen for bacterial examination onehundred twenty three samples were culture on special media forMycobacteria . The result revealed that four rats were infected withMycobacteria . four isolates of Mycobacteria two isolate from Lung , twoisolate from Liver . The morbidity rate with Mycobacteria was 9.9% .